Determinants of Anemia among HIV-Positive Children on Highly Active Antiretroviral Therapy Attending Hospitals of North Wollo Zone, Amhara Region, Ethiopia, 2019: A Case-Control Study - Biruk Beletew; Ayelign Mengesha; Mohammed Ahmed; Awet Fitwi; Mesfin Wudu (Anemia)
Introduction. Anemia is one of the most commonly observed hematological abnormalities and an independent poor prognostic marker of HIV disease. The rate of progression and mortality in this subgroup of patients is high compared to nonanemic patients. WHO estimates that over two billion people are anemic worldwide and young children bear the world’s highest prevalence rate of anemia. In Ethiopia, there is limited information about the determinant factors associated with anemia among HIV positive children. Thus, this study aimed to determine the determinant factors of anemia among HIV-infected children on HAART. Objective. The main purpose of this study was to assess the determinants of anemia among children on highly active antiretroviral therapy attending hospitals of North Wollo Zone, Amhara Region, Ethiopia. Methods. A case-control study was conducted on 350 HIV-infected children on HAART attending Hospitals of North Wollo Zone, from February 1 to March 30, 2019. The study participants were selected with a consecutive sampling technique. An adapted, interviewer-administered, and pretested questionnaire and chart review were employed to collect the data. Besides, blood and stool samples were investigated to determine hematologic indices and malaria and to investigate intestinal parasites, respectively. Data were analyzed by using the SPSS version 24 statistical software and bivariate and multivariate logistic regression was used to identify predictors. Results. A total of 350 HIV positive children (117 cases and 234 controls) were included in this study with an overall response rate of 100%. On multivariate analysis, variables which have spastically significant association with anemia were as follows: had amebiasis (AOR = 7.29, 1.22–43.56), had history of opportunistic infections (AOR = 9.63, 1.94–47.85), had malaria infection (malaria pf) (AOR = 4.37, 1.16–16.42), eating nondiversified food (AOR = 10.39, 2.25–48.0), WGT-Age Z score value between −2_−3 (AOR = 9.80, 2.46–39.14), level of adherence (AOR = 2.31, 1.92, 7.77), and being from a rural area (AOR = 8.8, 2.07–37.79). Conclusion. In this study, having parasitic infections, having a history of opportunistic infections, being malnourished, having poor adherence to ART, caregivers living in the rural area, and eating nondiversified foods were significantly associated with hemoglobin status. Therefore, intervention aimed at prevention, early diagnosis, and treatment of anemia is essential in these patients.